Ascaris lumbricoides, an uncommon cause of appendicitis - Ruelas-Contreras, Cesar H.; Caballero-Concha, Estefania (International Surgery Journal, 2023)
Appendicitis is the first cause of acute abdomen. There are many causes of appendicitis, one of them is parasites, and, Ascaris is the most common helminth infection in tropical countries (Asia, Africa, South America). Ascaris, once it is ingested, lives at the digestive tract and it can end up in the appendix lumen and lead to appendicitis by luminal obstruction, in fact this presentation is rare and is still debatable in the literature. Diagnostic most of times is made retrospectively by the demonstrations of ascaris eggs on the pathological examination of the appendix. We present the case of 7 years old male that arrives to emergency room presenting clinically acute appendicitis with 24 hours from beginning with fever 38ºC, intense mesogastrium abdominal pain with migration to right lower quadrant, anorexy, without nausea or vomiting, normal vital signs at physical examination intense abdominal pain, rebound, positive McBurney and psoas sign, leukocytosis with sift left. He underwent to emergency operation because suspect of appendicitis, we found a cecal appendix with Ascaris lumbricoides parasite in its lumen.